HIGHER EDUCATION AS THE MOST IMPORTANT CHANNEL FOR ELITE TRAINING - I. I. Rozhkov (Дискурс, 2017)
The article highlights the crucial role of higher education as an important factor in the development of human potential for the economic and social development of the society. The structure of education and higher education, as well as the close connection between education and upbringing and the role of higher education as a tool for elite training are analyzed. A meritocratic approach to the study of elites and the specifics of its application in the present are considered. The role of moral factors in the activity of elites in the context of the analysis of elitism and mass character as two sides of higher education is revealed.